Development and Evaluation of the Quality of Life Scale for Children With Visual Impairments in China - Liu, Jie; Evans, Richard; Wang, Yanjun; Hu, Beibei; Tong, Yan; Li, Shaoqiong; Tian, Zhiqiang; Li, Jing; Zhang, Cuihua; He, Lu; Zheng, Jianzhong (Frontiers in Pediatrics, 2022)
Background: Visual impairments related to non-correctable vision loss, including blindness and low vision, have been consistently shown to lower a person’s health-related quality of life. This study assessed the reliability, validity, and discrimination of the Quality of Life Scale for Children with Visual Impairments (QOLS-CVI) in China. Methods: The Pediatric Quality of Life Inventory™ 4.0 and World Health Organization Quality of Life-Disability Scale for physical disability were selected to define conceptual frameworks and item libraries based on relevant existing studies. According to two rounds of expert consultations and group discussions, some items were modified, and the draft scale was developed. Two item selection processes based on classical test theory and item response theory were used to conduct a preliminary survey and a formal survey in special schools in Shanxi and Hebei Provinces. Finally, the reliability and validity of the quality of life scale for visually impaired children in China were verified. Results: The final QOLS-CVI consisted of 38 items, 10 subdomains, and 6 domains. Reliability was verified by Cronbach’s alpha coefficient, split-half reliability, and test-retest reliability (Cronbach’s alpha for the full scale, 0.841; split-half reliability, 0.629; and test-retest reliability, 0.888). The validity results showed that the multidimensional scale met expectations: exploratory factor analysis and confirmatory factor analysis indicated good fitting models for children with visual impairments. Conclusions: The QOLS-CVI was determined to be reliable and valid and to have strong feasibility and effectiveness. This scale can be used as an evaluation tool to study the QOL and social-participation ability of children with visual impairments.